Tortilleras Negotiating Intimacy : Love, Friendship, and Sex in Queer Mexico City - Russo, Anahi (Book collections on Project MUSE., 2020)
"Tortilleras Negotiating Intimacy: Love, Friendship, and Sex in Queer Mexico City is the first ethnography in English to focus primarily on women's sexual and intimate cultures in Mexico. The book shows the transformation of intimacy in the lives of three generations of women in queer spaces in contemporary Mexico City, as their sexual citizenship changes, including references to same-sex marriage and anti-discrimination laws. The book shows how these individuals reconfigure relationships through marriage, polyamory, friendship, and sex. Tortilleras Negotiating Intimacy suggests that "new" intimate cartographies are emerging in Mexico City, ultimately redefining relationships, gender, and mexicanidad. Building on ethnographic data collected over the past decade, including 45 in-depth interviews with women between the ages of 22 and 65 participating in LGBT spaces, Tortilleras Negotiating Intimacy shows how lesbian women (mainly cis, but some trans) negotiate friendship, same-sex marriage, polyamory, and sexual practices, reinventing love, eroticism, friendship, and ultimately the social organization of Latin American societies"--